2001
DOI: 10.1063/1.1353194
|View full text |Cite
|
Sign up to set email alerts
|

The spectral linewidth of tunable semiconductor InAsSb/InAsSbP lasers emitting at 3.2–3.6 μm (2800–3100 cm−1)

Abstract: A method was used to measure the width of emission lines of a type of semiconductor laser with composition InAsSb/InAsSbP. This type of laser was manufactured specially for absorption high-resolution spectroscopy of gases absorbing in the 2800–3100 cm−1 region. Parameters used for calculation of spectral emission linewidths were obtained using selected rotation-vibration lines of the gaseous molecules N2O, CH3Cl, and OCS. The estimated spectral emission linewidths varied in the range 10–30 MHz in dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…An interesting result is that our laser profile is much better described with a single Gaussian shape than a Lorentzian. Our line widths are considerably larger than those we measured [20] for conventional edgeemitting diode lasers operating in a temperature range 20 -80 K.…”
Section: Conclusion 31 the Spectral Widthcontrasting
confidence: 62%
See 1 more Smart Citation
“…An interesting result is that our laser profile is much better described with a single Gaussian shape than a Lorentzian. Our line widths are considerably larger than those we measured [20] for conventional edgeemitting diode lasers operating in a temperature range 20 -80 K.…”
Section: Conclusion 31 the Spectral Widthcontrasting
confidence: 62%
“…This work follows our previous studies, when the FTIR spectrometer [18] was used for the diagnostic of the room temperature operating a distributed Bragg reflector stripe GaInAsSb/AlGaAsSb based diode laser [15] and laser width of the 66 K InAsSb/InAsSbP laser diode [19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Con− sideration of physical processes taking place in tunable lasers with a smooth waveguide of different geometric para− meters suggests a heavy dependence of the lasing linewidth on both the concentration of non−equilibrium charge car− riers N and the volume of the active region [32]. We pub− lished several articles where we continued our earlier inves− tigations of the properties of the tunable laser diodes based on InAsSb/InAsSbP [29,[31][32][33][34] with smooth waveguide in cavity where nonequilibrium carrier concentration has a gradient from the middle to the end of the cavity.…”
Section: Measurement Of Laser Linewidthmentioning
confidence: 87%
“…In the previous papers [31][32][33][34] we demonstrated that lasers with a smooth waveguide yield the narrow spectral linewidth Df. Study of the dependence of the laser linewidth on the structural prop− erties of the laser crystal indicated that small differences in Df in all lasers are not caused by defects in the crystals or random defects, but rather by physical processes involving interactions of the radiation with nonequilibrium charge car− riers.…”
Section: Measurement Of Laser Linewidthmentioning
confidence: 96%
See 1 more Smart Citation